2013
DOI: 10.1371/journal.pone.0070056
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Vaccination Reduced Effector Memory CD4 T Cells and Induced Effector Memory Treg Cells for Type I Diabetes Treatment

Abstract: BackgroundVaccination could induce immune tolerance and protected NOD mice from the development of type I diabetes (T1D). We previously demonstrated that insulin peptide (B9-23) combined with dexamethasone (DEX) stimulated the expansion of antigen specific regulatory T (Treg) cells which in turn effectively prevented T1D in NOD mice. Here, we aimed to investigate the therapeutic effect of tolerogenic vaccination for T1D treatment.Methodology/Principal FindingsThe diabetic NOD mice (Blood glucose level ≧250 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…It seems that, presentation of SP‐derived peptides from endogenous PPI production was still able to sustain the T CM and T EFF population. Animal studies have also shown that insulin‐based immunotherapy or peripheral proinsulin expression reduces CD4+ T EM subsets by inducing Tregs . In a similar study, Martinuzzi et al using ELISpot assay, reported a significant reduction in the PPI‐specific IFN‐γ producing CD8+ T cells, illustrating decline in T cell responses following insulin therapy in T1D subjects.…”
Section: Discussionmentioning
confidence: 88%
“…It seems that, presentation of SP‐derived peptides from endogenous PPI production was still able to sustain the T CM and T EFF population. Animal studies have also shown that insulin‐based immunotherapy or peripheral proinsulin expression reduces CD4+ T EM subsets by inducing Tregs . In a similar study, Martinuzzi et al using ELISpot assay, reported a significant reduction in the PPI‐specific IFN‐γ producing CD8+ T cells, illustrating decline in T cell responses following insulin therapy in T1D subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Because administration of peptide Ag together with immunomodulatory reagents favors the induction of Ag-specific Tregs in vivo (32,53,54), we assume it should be desirable to include islet Ag peptide in the combination, and indeed such a combination promoted significant Ag-specific Treg expansion in the spleens and pancreatic lymph nodes (Fig. 2B, 2C).…”
Section: Discussionmentioning
confidence: 99%
“…Third, parents may not be able or willing to overcome barriers, like missing work or school, for their children's SIV. According to our previous study, 17 we assumed this phenomenon would be more significant among migrant children, whose parents had not enough time for primary healthcare and were less aware of the information on vaccination. Furthermore, the poorer education level of migrant parents would also influence their awareness and capacity to seek and take advantage of vaccination service and other public health service.…”
Section: Discussionmentioning
confidence: 99%